Bridging method and practice: Toward a balanced approach to statistical modeling in occupational medicine and psychology - Francesco CHIRICO (GIornale Italiano di Psicologia e Medicina del Lavoro, 2025)
Statistical modeling plays a pivotal role in occupational medicine and psychology, offering essential tools to understand complex interactions between workplace factors and employee health. However, the growing sophistication of analytical techniques risks reducing their practical relevance if models become too complex for real-world application. This editorial advocates for a balanced approach that combines methodological rigor with operational usability. Drawing on recent research examples, it highlights the need for simplicity, transparency, validation, and user-centered design to ensure that statistical models translate into actionable strategies for improving workplace well-being. Only through such an approach can statistical modeling bridge the gap between academic theory and occupational health practice.